(untitled) (Baghdad Science Journal, 2005)
Been manufacturing detector Altosalih optical pattern contact metal semiconductor through deposition poles of aluminum metal on the chips of crystal cadmium Tleraad (CdTe) with directional [111] and growing with laboratory and annealed at a temperature 80c for 30 minutes and eat Study of some electrical properties nailed and scoutNmadj ??????? copper with non ??????? models to see effect Alichoab well research deals impact Alichoab and frequency detector resistance